If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(2b + 3c) = 0 (2b * a + 3c * a) = 0 (2ab + 3ac) = 0 Solving 2ab + 3ac = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'a'. a(2b + 3c) = 0Subproblem 1
Set the factor 'a' equal to zero and attempt to solve: Simplifying a = 0 Solving a = 0 Move all terms containing a to the left, all other terms to the right. Simplifying a = 0Subproblem 2
Set the factor '(2b + 3c)' equal to zero and attempt to solve: Simplifying 2b + 3c = 0 Solving 2b + 3c = 0 Move all terms containing a to the left, all other terms to the right. Add '-2b' to each side of the equation. 2b + -2b + 3c = 0 + -2b Combine like terms: 2b + -2b = 0 0 + 3c = 0 + -2b 3c = 0 + -2b Remove the zero: 3c = -2b Add '-3c' to each side of the equation. 3c + -3c = -2b + -3c Combine like terms: 3c + -3c = 0 0 = -2b + -3c Simplifying 0 = -2b + -3c The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
a = {0}
| 6v^2-23+10=0 | | -6x-12=6x+8 | | -4z(z-7)=0 | | -4(3-7x)= | | 6+2y=12.2 | | -6x-12=3x+8 | | 3y-2=2.26 | | 3(x+5)-2x+12= | | 7(314)-75(21)-2(259)=x(10+5) | | -2.22=m/4-5 | | 3[z-(6z+15)+5]=3(z+2) | | 1.3+2.3=2.3-2.3 | | Y+6+y=28 | | 7(314)-75(21)-2(259)=x(3+5) | | 1.2=4s-11.2 | | -7(x-8)=9-6x | | 11w-81=744 | | -8-5n=64+3 | | -2y^2-14y+7=0 | | 8[5-8(x-1)]+7[(5x+6)-8]=11x-341 | | .8=ln(y) | | 0=x^2+2x-63 | | 4x+4x=7x-9 | | 5y(y-2)=6-3y | | 4.7x+2=3.2x-4 | | 40x+4(1.5x)=736 | | 4(x-6)-(x+2)=-12 | | g/6-17=1 | | 4x-3+2=8x-3-x | | -8+2x=4 | | 16=10-1/4m | | graphy=-x^2+4x-7 |